Verbs of intermittent-softening mode of action - Sahakyan David Arsenovich (Zien Journals, 2022)
The article presents a fragment of the description of verbs of the intermittentsoftening mode of action of the modern Russian language. The theories of M.A. Shchelyakin, Prokopovich E.N. and others are considered
Keywords: Glagols of intermittent-softening mode of action; Glagols of intermittent-softening mode of actionsuffix; iterative suffixes